Influence of buccal bone wall thickness on the peri‐implant hard and soft tissue dimensional changes: A systematic review. Issue 3 (5th February 2023) - Monje, Alberto; Roccuzzo, Andrea; Buser, Daniel; Wang, Hom‐Lay
Abstract: Background: The significance on the association between the peri‐implant bucco‐lingual dimension (BLD) at the stage of implant placement and the occurrence of biological and esthetic complications is yet unknown. Material and methods: Systematic screening of electronic sources was carried out to identify clinical and preclinical studies reporting on the baseline BLD and/or buccal bone thickness (BBT) values. A secondary objective was to assess the effect of simultaneous grafting at sites with deficient or no buccal bone wall (BBW) at baseline. The primary outcome variables were BBT, BLD, and buccal vertical bone loss (VBL) at re‐evaluation. Moreover, radiographic, clinical, and patient‐reported outcome measures (PROMs) were evaluated. Results: Overall, 12 clinical and four preclinical studies met the inclusion criteria. Inconsistencies were found in defining the critical BBT across the clinical and preclinical data evaluated. The clinical evidence demonstrated that during healing, dimensional changes occur in the alveolar bone and in the BBW that may compromise the integrity of the peri‐implant bone, leading to VBL and mucosal recession (MR), particularly in scenarios exhibiting a thin BBW. The preclinical evidence validated the fact that implants placed in the presence of a thin BBW, are more prone to exhibit major dimensional changes and VBL. Moreover, the clinical data supported that, in scenarios where dehiscence‐type defects occur and are left for spontaneous healing, greater VBL and MR together with the occurrence of biologic complications are expected. Furthermore, the augmentation of dehiscence‐type defects is associated with hard and soft tissue stability. PROMs were not reported. Conclusions: Dimensional changes occur as result of implant placement in healed ridges that may lead to instability of the peri‐implant hard and soft tissues. Sites presenting a thin BBW are more prone to exhibit major changes that may compromise the integrity of the buccal bone and may lead to biologic and esthetic complications.